THE INFLUENCE OF PRODUCT QUALITY, PRICE, AND BRAND IMAGE ON CUSTOMER LOYALTY OF MACAN HITAM RICE IN JEMBER REGENCY - Hardiyani, Rini; Al Ardi, Aditya Nizar; Nadhirah, Aulia; Saadillah, Dinu (GEMAH RIPAH: Jurnal Bisnis, 2025)
Jember consumer loyalty as a function of product quality, pricing, and brand perception is the intended outcome of this research. One hundred customers served as the sample for this research. Product quality, pricing, and brand image served as independent variables in this study, with customer loyalty serving as the dependent variable. By administering surveys to pre-existing samples, this research made use of quantitative descriptive analysis. The researchers in this study used a 5-point Likert scale. This study employs SPSS software for data processing. One important takeaway from the data is that product quality does, in fact, influence consumer loyalty. 2) The loyalty of customers is greatly affected by price. (3) customer loyalty is strongly influenced by brand image; (4) customer loyalty is simultaneously affected by product quality, price, and brand image